Risky writing: working with a heteroglossic pedagogy to deepen pre-service teachers’ learning - Mendelowitz, Belinda; Dixon, Kerryn (Faculty of Education, University of the Free State, 2016)
This article explores how course design and assessment in a first year pre-service teacher education course for English students can be imbued with academic depth and rigour in ways that enable students to take intellectual and textual risks. We argue for a conceptualisation of risky writing in which we open up student critical engagement with sociolinguistic issues by juxtaposing academic and creative genres in curriculum course material and assessment. Academic writing in its current form is problematised and questions are raised about the extent to which academic courses provide students with an apprenticeship into compliance, conformity and silence. We present the possibilities of using a heteroglossic pedagogy (Blackledge & Creese, 2014) for learning, teaching and writing. The principles underpinning the course (linguistic diversity as a resource, the value of lived experience and the interrelation of epistemological access and academic rigour) constitute a heteroglossic pedagogy. We illustrate these principles using two examples, one from student performance during the course and the second from independent writing for an assignment. Together, the two data snapshots illustrate the pedagogic possibilities of fluid movements between distantiation and appropriation using flexible genres, which ultimately facilitate deeper student engagement and understanding of disciplinary knowledge. The two data snapshots are not “mere descriptions or anecdotes” detached from principles (Slonimsky & Shalem, 2004: 92). They facilitate academic depth and rigour because of the carefully staged moves between the strange and the familiar in a context that encourages students to take creative and intellectual risks.
Keywords: Heteroglossia; Heteroglossic pedagogy; Academic writing; Risk; Critical engagement; Creative genres; Distantiation; Appropriation